A Tale of Two Species : Revisiting the Effect of Registration Reform on Informal Business Owners in Mexico - Bruhn, Miriam (Elsevier, 2013)
Some argue that informal business owners are viable entrepreneurs who do not register due to complex regulation. Others claim that they are making a living while searching for a job. This paper suggests that a mix of both views is correct. I separate informal business owners into those who have characteristics similar to wage workers and to formal business owners and study the impact of a business registration reform in Mexico on these two species. Informal business owners from the wage worker species are less likely to register due to the reform, but more likely to become wage workers since the reform created jobs. Informal business owners from the formal business owner species are more likely to register, but only in municipalities with high pre-reform constraints to formal entrepreneurship. These results explain why Bruhn, 2008 and Bruhn, 2011 finds no effect of the reform for all informal business owners taken together.